Jahrbuch für Kulturpolitik 2015/16 Transformatorische Kulturpolitik - Sievers, Norbert; Föhl, Patrick S.; Knoblich, Tobias J. (Jahrbuch für Kulturpolitik, 2016)
With the realisation of German unity, cultural policies have also changed - conceptually as well as instrumentally. It would be too short-sighted, however, if one were to frame this transformation as the direct result of German unity. It is also necessary to take into account that it occures in the context of a not only European but also global social shift. The "2015 Yearbook for Cultural Politics" contains the contributions from the eighth Federal Congress for Cultural Politics, entitled "Kultur.Macht.Einheit?" ("Culture.Power.Unity?"), which featured presentations be figures such as Monika Grütters, Wolfgang Thierse, Norbert Lammert, and Tim Renner. Additional articles extrapolate on this extensive field and broaden the range of perspectives on the phenomenon of transformation.